'Green Tide' to Biochar: Preparation and Adsorption Isotherms for Three Typical Organic Pollutants. (March 2018) - Ma, Yuhui; Wang, Jing; Zhang, Yushan
Enteromorpha prolifera (EP), the main source contributing to the outbreak of 'green tide', was used as the raw material to prepare biochars by pyrolysis. The biochars were analysed using N2 -adsorption and Fourier transform infrared (FTIR) spectroscopy. The pyrolysis process was investigated by thermogravimetric analysis coupled with FTIR. The adsorption capacities of the biochars were compared in terms of removal efficiencies of methylene blue (MB), oxytetracycline (OTC) and humic acid (HA). The adsorption isotherms of the three organics by the optimum biochar were investigated. The results showed that the Brunauer–Emmett–Teller surface area of the biochar increased from 36 to 643 m 2 g −1 with increasing pyrolysis temperature. The surface functional groups contained in EP were damaged during pyrolysis, while–N=O, S=O and C=N groups were formed on the biochar surface. Decomposition of EP resulted in the vigorous release of gaseous products at 240 °C, including CO2, H2 O, aldehydes, ethers, aliphatic amines, sulfones and alcohols. CO2 was released due to the decomposition of carbonates above 700 °C and the in situ reduction of CO2 by carbon contained in the biochar was responsible for the high surface area of the biochar prepared at 750 °C (EPC750). EPC750 had the highest adsorption capacities for MB, OTC and HA among the biochars. The adsorption equilibrium data for MB and OTC onto EPC750 followed the Langmuir model with monolayer adsorption capacities of 138.89 and 103.31 mg g −1 respectively. The adsorption data for OTC also exhibited good agreement with the Freundlich model, suggesting the adsorption process was controlled by multiple mechanisms. The adsorption of HA by EPC750 followed the Freundlich model and the maximum adsorption capacity reached 64.27 mg g −1 under the experimental conditions.